Effect of nitrate administration on plasma nitric oxide levels in patients with peripheral arterial disease at Dr. Sardjito General Hospital, Yogyakarta - Arditya Damarkusuma; Muhamad Taufik Ismail; Hariadi Hariawan; Sherly Primasari Agus (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Peripheral arterial disease (PAD) is a disease involving reduction of blood flow to the inferior extremity associated with atherosclerotic lesions. In 2010, more than 200 million people with PAD were reported globally, including 54.8 million in Southeast Asia. The high prevalence of PAD causes its management become challenging for clinicians. Nitric oxide (NO) has a role in endothelial function that is associated with the appearance of symptoms in PAD patients. Exogenous nitrate is usually used as a primary vasodilator in the treatment of angina pectoris and Prinzmetal angina. However, information concerning the role of nitrate administration to improve symptomatic PAD patients is limited. This study aimed to evaluate the effectiveness of exogenous nitrates in increasing plasma NO levels and improving PAD patients. A prospective pre-post clinical trial involving PAD patients who were registered in the vascular registry at Dr. Sardjito General Hospital, Yogyakarta  was conducted. Primary endpoint was the change in plasma NO levels after short term administration of nitroglycerin oral 2.5 mg once daily (4 h) and long term (7 d). Analysis of variance test with Bonferroni posttest was used for statistical hypothesis testing. Among 33 subjects who completed this study, no negative side effects, and only one hypotensive patient was reported at the first follow-up after 4 h of the nitroglycerin administration. Plasma NO levels increased in the post 4 h and in the post 7 d administration. However, no statistically significant was observed (p > 0.05). Administration of exogenous nitrates in patients with PAD increases the plasma NO levels, even though it is not statistically significant.